MRI-guided focused ultrasound ablation of lumbar medial branch nerve: Feasibility and safety study in a swine model. (2nd October 2016) - Kaye, Elena A.; Monette, Sebastien; Srimathveeravalli, Govindarajan; Maybody, Majid; Solomon, Stephen B.; Gulati, Amitabh
Abstract: Purpose: About 10–40% of chronic low back pain cases involve facet joints, which are commonly treated with lumbar medial branch (MB) radiofrequency neurotomy. Magnetic resonance imaging-guided focused ultrasound (MRgFUS), a non-invasive, non-ionising ablation modality used to treat tumours, neuropathic pain and painful bone metastasis can also be used to disrupt nerve conduction. This work's purpose was to study the feasibility and safety of direct MRgFUS ablation of the lumbar MB nerve in acute and subacute swine models. Materials and methods: In vivo MRgFUS ablation was performed in six swine (three acute and three subacute) using a clinical MRgFUS system and a 3-T MRI scanner combination. Behavioural assessment was performed, and imaging and histology were used to assess the treatment. Results and conclusions: Histological analysis of the in vivo studies confirmed thermal necrosis of the MB nerve could be achieved without damaging the spinal cord or adjacent nerve roots. MRgFUS did not cause changes in the animals' behaviour or ambulation.